Birth and propagation of optical vortices in helico-conical optical beams - Hermosa, Nathaniel P. II
Singular optical physics is a new branch of optics that deals primarily with optical vortices. An optical vortex is a line of phase singularity where the complex scalar field vanishes at its position. At the center of the vortex, the phase gradient is infinite and the intensity of the beam vanishes even when it is focused. Optical vortices interact similar to particles. They repel or attract, split or annihilate or be born as different sets of optical vortices. There have been studies in past that deal with the propagation of dynamics of beams that are not solutions of the Paraxial Wave Equation, and their discussion is centered on the evolution and the interaction of optical vortices that are produced when the beams are propagated. The object of this dissertation is to investigate the propagation of Helico-Conical Optical Beams (HCOBs). The conical phase of this beam is being fractured by a helical phase which is the phase of an optical vortex. Emphases were given to the birth and propagation of optical vortices in these beams. In this dissertation the beams are produced by computer-generated holograms. Their phase profiles are examined using Mach-Zehnder interferometry. A string of similar charged optical vortices are seen arising as the beams are propagated. We report that optical vortices bahave as point vortices in hydrodynamics. We also propagated the beams numerically with the scalar diffraction theory. We divide the analysis of the propagation into two regions - regions of birth of the optical vortices and the region where they interact with each other and with the background beam. Optical vortices appear every 2π cut in the wavefront. The vortices interact by the warping of the phase by another vortex near them. These are verified experimentally. The results in this dissertation offer better understanding of the propagation dynamics of beams with a conical phase with embedded optical vortices, which may find application in optical trapping, optical data storage and optical switching as well as suggest some insights to some fundamental questions in similar systems in superfluidity and in Bose-Einstein condensates.